Health impacts of small reservoirs in Burkina Faso - Boelee, Eline; Cecchi, P.; Koné, A. (International Water Management Institute, 2009)
In Burkina Faso, at least 1,700 small reservoirs have been constructed, most of them during the last 30 years. Numerous and scattered, these beneficial multipurpose systems combine productive with domestic water uses. However, their environmental and health impacts remain insufficiently documented. This report combines data from different sources into syntheses and national maps, with a focus on water-related diseases. The mitigation of negative impacts requires an integrated approach to specifically identify the enhancing and limiting factors that influence environmental impacts and the transmission of diseases around reservoirs. Public awareness campaigns need to accompany the promotion of preventive and curative measures and the development of alternative water sources for domestic supply.